Peran Tenaga Kefarmasian dalam Penanggulangan Bencana Role of Pharmacist in Disaster Management - Faradilla, Meutia (Pharmaceutical Sciences and Research, 2018)
Indonesia is a country that has high potency to be affected by disaster, either by natural or man-made disaster. After the 2004 tsunami, Indonesian government has improved its disaster prevention policy and program. In disaster management study, health management in disaster setting is aimed to assure the implementation of health service toward victims accordingly. As integrated part of the healthcare team in disaster management, pharmacists have to understand the importance of pharmaceutical care in pre-disaster, disaster, and post-disaster phase. This article aims to provide an overview on pharmacists’ role in disaster management from preparing and distributing medicine and medical devices to its role in therapy management, counselling, and patient education. This article also proposes to stakeholders in pharmacist professional organization to arrange plan and policy to increase and improve pharmacists’ involvement in disaster management.